Analisis Prediksi Kebangkrutan dengan Menggunakan Metode Altman Z-Score, Springate, Zmijewski dan Grover Pada PT. Hero Supermarket, Tbk Periode 2019-2022 - Ratno Sarwanto; Hari Setiono; Nur Ainiyah (Jurnal Kendali Akuntansi, 2023)
The purpose of this study is to determine the financial condition of PT. Hero Supermarket Tbk using the Altman Z-Score, Springate, Zmijewski, and Grover methods for the 2019-2022 period. This type of research is quantitative descriptive research. The sample used in this study was PT. Hero Supermarket Tbk with simple random sampling as its sampling technique. The data used in this study is secondary data, namely financial statements obtained from the Indonesia Stock Exchange. The results of this study show that PT Hero Supermarket Tbk's Altman Z-Score, Springate, and Grover methods for four years on average have the same results, namely in 2019 the company was in good health. Meanwhile, in 2020-2022, PT Hero Supermarket Tbk went bankrupt. Unlike the three methods above, Zmijewski's method in 2019 and 2020 the company was in bankruptcy. But in 2021 and 2022 the company was in good health